Thrombosis of aneurysmal pulmonary arteries in patent ductus arteriosus with Eisenmenger syndrome - Deepanjan Bhattacharya; Deepa Sasikumar; K N Harikrishnan Kurup; Ayyappan Anoop; Sravan Kumar Gaddamedi (Wolters Kluwer Medknow Publications, 2022)
A 45-year-old lady with patent ductus arteriosus with Eisenmenger's syndrome had presented with hemoptysis. Computed tomography revealed aneurysmally dilated pulmonary arteries with a large calcified organized thrombus.